Biology of IL-36 Signaling and Its Role in Systemic Inflammatory Diseases - Yuan, Zhi-Chao; Xu, Wang-Dong; Liu, Xiao-Yan; Liu, Xing-You; Huang, An-Fang; Su, Lin-Chong (Frontiers in Immunology, 2019)
Interleukin (IL)-36 is a member of the IL-1 superfamily and includes three agonists (IL-36α, IL-36β, and IL-36γ) and an antagonist (IL-36Ra). IL-36 agonists bind to heterodimeric receptor complexes. Then, the heterotrimer complexes signal via intracellular functional domains, binding to downstream signaling proteins and inducing inflammatory responses. In this review, we summarized the current knowledge about the biological role of IL-36 and its correlation with systemic inflammatory diseases. The information collected will help to increase the understanding of the potential of IL-36 and may give clues for developing novel therapeutic strategies.